Potensi Debit Aliran Lokal Waduk Saguling Menggunakan Model Hujan Limpasan - Asep Ferdiansyah; sri mulat yuningsih; Mirwan Rofiq Ginanjar; Isnan Fauzan Akrom (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2020)
Saguling reservoir is one of the three largest reservoirs in the Citarum River Basin. The water source of its reservoir originates from Upper Citarum river basin, with gauging station located in Citarum-Nanjung and local discharge from tributaries around the reservoir. The problem is there is no observation of local discharge from the tributaries, thus its potential is estimated. The purpose of this study is to analyze the potential of local discharge with the Hydrology Engineering Center-Hydrologic Modeling System (HEC-HMS) model. The HEC-HMS Rainfall-runoff method is used for calculating the potential of the local discharge that flows into Saguling resevrvoir. The parameters used in the model are deficit constant (loss parameter), linear reservoir (baseflow parameter), dan lag time (transform parameter). Rainfall-runoff model produced good calibration values for Citarum-Nanjung Gauging Station with R2 of 0.8 and the Nash-Sutcliffe efficiency (NSE) value of 0.788. The verification result carried out in Saguling reservoir gives NSE of 0.8343 and R2 value of 0.83. The simulation shows that the potential discharge from local river contributes about 21.64% of the total discharge that enters into the reservoir with monthly dependable flow for power plants, Q80 and Q85 values at 8,23 m3/s and 5,69 m3/s, respectively. The average discharge of local rivers can generate electricity of 3.89 MW - 162 MW.Keywords: Local discharge, rainfall runoff, potential discharge, Saguling reservoir